Malmquist indices of productivity growth for islamic and conventional banks in Malaysia. - Yahya, Mohamed Hisham; Muhammad, Junaina; Abdul Hadi, Abdul Razak (David Publishing Company, USA, 2010)
This paper studies the total factor productivity (TFP) of banks in Malaysia with the emphasis on comparing the relative productivities of Islamic and Conventional banks. The Malmquist index approach is used to decompose productivity growth into technical efficiency and technological change. The productivity growth is measured and decomposed into technical change and efficiency change. The efficiency change is further decomposed into pure efficiency change and scale efficiency. It is found that Islamic banks’ productivity growth is limited by its lack of technological change compared to its conventional counterparts. Nonetheless, both types of banks are operating at the correct level in terms of scale or size.